The roles of community fruit garden (tembawang) on maintaining forest structure, diversity and standing biomass allocation: an alternative effort on reducing carbon emission - DWI ASTIANI; RIPIN RIPIN (Biodiversitas Journal of Biological Diversity, 2016)
Astiani D, Ripin. 2016. The roles of community fruit garden (tembawang) on maintaining forest structure, diversity and standing biomass allocation: an alternative effort on reducing carbon emission. Biodiversitas 17: 359-365. Fruit garden (tembawang) Cempedak Village in Sanggau West Kalimantan has been established by local community for their family mixed garden ~ >100 years. The families of 3rd generation were utilizing the tembawang for their needs of building materials, fire woods, rattan, vegetables, fruits, and traditionals medicine. It is important to study how this tembawang play their roles in maintaing forest structure, species diversity and stocking biomass. In 2014, we studied this area for exploring the vegetation composition and their ability to stock biomass of the tembawang. Stratified Random Sampling was applied to the 6.69 ha tembawang area, which devided into three major land cover patches (Mixed fruit garden, mixed rubber plants, and fruit garden mixed with apik-Arenga undulatifolia Becc palm). We surveyed and sampled vegetation using transect methods purposively chosen on each landcover patch, with sampling area consecutively for mixed fruit garden, mixed rubber plants, and mixed of fruit garden and apik were 1.52, 0.6, and 0.72 hectars. Results demonstrated that mixed fruit garden carried out higher tree diversity, density, basal area, and maintained the largest above ground biomass per hectar compared to the two other patches. From 97 vegetation spesies registered, it maintained 49 tree species of diameter >20cm and 51 tree species in the lower strature in the forest structure. Interestingly, Durio zibethinus Murr. was a dominant species on all landcover patches types and sinked the largest above ground living biomass. The choice of fruit species on tembawang determined the capability of the embawang land to sequester and stock carbon in trees, because the trees were standing in tembawang for longer time compared to the one in production forest. This results show that, beside its multiple role for people community, tembawang provide other benefits to the nature in maintaining forest structure, diversity, and stocking large carbon in standing biomass.